2002
DOI: 10.1128/mcb.22.19.6681-6688.2002
|View full text |Cite
|
Sign up to set email alerts
|

The GCN2 eIF2α Kinase Is Required for Adaptation to Amino Acid Deprivation in Mice

Abstract: The GCN2 eIF2␣ kinase is essential for activation of the general amino acid control pathway in yeast when one or more amino acids become limiting for growth. GCN2's function in mammals is unknown, but must differ, since mammals, unlike yeast, can synthesize only half of the standard 20 amino acids. To investigate the function of mammalian GCN2, we have generated a Gcn2 ؊/؊ knockout strain of mice. Gcn2 ؊/؊ mice are viable, fertile, and exhibit no phenotypic abnormalities under standard growth conditions. Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
325
0
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 401 publications
(345 citation statements)
references
References 45 publications
(53 reference statements)
15
325
0
5
Order By: Relevance
“…As ATF4 has been reported to regulate the transcription of many tRNA synthetases 25,3032 , we next compared the expression of WARS to that of all other tRNA synthetases in U87-MG glioblastoma cells that were Trp starved for 24 h. Trp starvation most strongly induced WARS mRNA expression (2,6 fold; Figure 4O). In addition, 7 other tRNA synthetases (glycyl-tRNA synthetase, GARS; cysteinyl-tRNA synthetase, CARS; alanyl-tRNA synthetase, AARS; methionyl-tRNA synthetase, MARS; seryl-tRNA synthetase, SARS; tyrosyl-tRNA synthetase, YARS and glutamyl-prolyl-tRNA synthetase, EPRS) were upregulated more than 1.5 fold.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As ATF4 has been reported to regulate the transcription of many tRNA synthetases 25,3032 , we next compared the expression of WARS to that of all other tRNA synthetases in U87-MG glioblastoma cells that were Trp starved for 24 h. Trp starvation most strongly induced WARS mRNA expression (2,6 fold; Figure 4O). In addition, 7 other tRNA synthetases (glycyl-tRNA synthetase, GARS; cysteinyl-tRNA synthetase, CARS; alanyl-tRNA synthetase, AARS; methionyl-tRNA synthetase, MARS; seryl-tRNA synthetase, SARS; tyrosyl-tRNA synthetase, YARS and glutamyl-prolyl-tRNA synthetase, EPRS) were upregulated more than 1.5 fold.…”
Section: Resultsmentioning
confidence: 99%
“…GCN2 is activated by sensing of uncharged tRNA and therefore should not be specific for Trp starvation 25,26 . In keeping with this, depletion of any essential amino acid resulted in an induction of WARS mRNA, albeit to different levels with depletion of Trp, valine and phenylalanine being the strongest inducers of WARS (Figure 4I).…”
Section: Resultsmentioning
confidence: 99%
“…For example, the PERK pathway has been shown to be activated by glucose deprivation and under hypoxic conditions (Koumenis et al 2002;Elanchezhian et al 2012). Similarly, amino-acid limitation also leads to attenuation of protein synthesis by phosphorylation of EIF2a phosphorylation via GCN2 kinase (Zhang et al 2002). Studies have also shown upregulation of CHOP in response to glucose and glutamine deprivation in both CHO and NSO cell lines (Murphy et al 2001;Lengwehasatit and Dickson 2002).…”
Section: Discussionmentioning
confidence: 99%
“…21,22 Amino acid depletion induces GCN2 kinase-mediated phosphorylation of eIF2α, leading to a global decrease in protein synthesis and induction of an adaptive survival program. 21,23 Under this condition, IRES-mediated translation of the Cat-1 and SNAT2 …”
mentioning
confidence: 99%
“…21,22 Amino acid depletion induces GCN2 kinase-mediated phosphorylation of eIF2α, leading to a global decrease in protein synthesis and induction of an adaptive survival program. 21,23 Under this condition, IRES-mediated translation of the Cat-1 and SNAT2 mRNAs occur, 24,25 thus preparing cells to transport amino acids once they become available. Methionine synthase, a key enzyme that clears intracellular homocysteine, is induced by its cofactor, vitamin B12, at a translational level through an IRES in the 5'UTR of the mRNA.…”
mentioning
confidence: 99%